Gender-specific social and environmental correlates of active travel to school in four European countries: the HBSC Study - Brindley, Catherina; Hamrik, Zdenek; Kleszczewska, Dorota; Dzielska, Anna; Mazur, Joanna; Haug, Ellen; Kopcakova, Jaroslava; Marques, Adilson; Altenburg, Teatske; Demetriou, Yolanda; Bucksch, Jens (Frontiers in Public Health, 2023)
Introduction Despite the health benefits, a large proportion of girls and boys in Europe do not travel to school actively. A better understanding of the correlates associated with this behavior could guide interventions. This study examines perceived social and environmental correlates of active travel to school (ACTS) from the 2017/18 Health Behavior in School-Aged Children (HBSC) survey in four European countries, with a special emphasis on gender differences (n = 22,023). Methods Logistic regression was conducted to analyze associations between the perceived importance of each correlate and ACTS behavior for 11-, 13-, and 15-year-old girls and boys from Germany, Czechia, Poland, and Slovakia. All models were adjusted for age, family affluence, and meeting World Health Organization recommendations for moderate-to-vigorous physical activity. Results Rates of ACTS significantly differed between girls and boys. In Czechia, 65% of girls and boys traveled to school actively, followed by Slovakia (61.4% girls and 58.4% boys), Poland (57.7% girls and 60.2% boys), and Germany (42.6% girls and 48.6% boys). Girls were less likely to actively travel to school compared to boys (odds ratio [OR]: 0.92, 95% confidence interval [CI]: 0.87–0.97). Increasing age (OR: 0.95, 95% CI: 0.93–0.97) and a greater distance to school index (OR: 0.89, 95% CI: 0.88–0.90) were both negatively associated with ACTS. The perceived importance of living closer to school and of road and neighborhood safety was positively associated with ACTS, with a stronger association in boys than in girls for neighborhood safety. On the contrary, the perceived importance of having people to walk with was negatively associated with ACTS, with a stronger association in girls (OR: 0.74, 95% CI: 0.65–0.84) than in boys (OR: 0.77, 95% CI: 0.66–0.88). Discussion This study provides insights into perceived social and environmental correlates associated with ACTS behavior. Future research should include gender-specific perceptions and more in-depth investigations of correlates encouraging ACTS, especially considering social aspects, safety issues, and the structuring of the environment in different cultural settings.